ChemInform Abstract: Copper‐Catalyzed Cycloaddition Between Secondary Phosphine Oxides and Alkynes: Synthesis of Benzophosphole Oxides. Issue 21 (6th May 2016) - Zhang, Pengbo; Gao, Yuzhen; Zhang, Liangliang; Li, Zhiqiang; Liu, Yan; Tang, Guo; Zhao, Yufen
Abstract: The use of phosphine oxides with substituted aryl moieties results in product mixtures due to rearrangement of the phosphorus substituent, e.